(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Viscosities and densities of 1,4 dioxane with hydrocarbon bromo benzene, ethyl benzene was measured over the entire mole fractions at temperatures ranging from 303.15, 308.15, and 313.15K. From these experimental results, excess molar volume VE and viscosity deviation ∆η was calculated. The VE and Δη exhibited positive and negative values, respectively, over the entire composition range in the order of 1,4 dioxane+ bromo benzene and < 1,4 dioxane +ethyl benzene systems. The outcomes indicated the weak interactions present in the mixtures. It exists mainly because of the number and position of methyl groups in these aromatic hydrocarbons. The molecular dynamics simulation studies for both the mixtures show no phase separation. The volume occupied by 1,4 dioxane + bromo benzene is lesser than 1,4 dioxane + ethyl benzene substantiating the experimental results of VE and Δη. Standard deviations from the Jouyban–Acree model between the fitting outcomes, and the calculated data are helpful deliberate mixing behavior of the binary mixtures. The molecular interactions existing between the components and comparison of liquid mixtures were also discussed.